Evaluation of nutritional behaviors and dietary supplement use of preschool children: A cross-sectional study from Türkiye - Zengin, Fatmanur Hümeyra; Çetin, Esra (Ankara Bilkent City Hospital, 2025)
Objective: This study aimed to evaluate preschool children’s (aged 3-6 years) nutritional behaviors and dietary supplement usage. Material and Methods: This descriptive, cross-sectional study was conducted between February 2024 and June 2024. The study sample consisted of 180 parents who live in the city center of Kastamonu. A questionnaire form including demographic characteristics of parents and children, children’s eating habits, and information about the dietary supplements used was applied. Results: The mean age of the children participating in the study was 60.9±9.3 months, and 35.6% of them used dietary supplements. The most commonly used supplements by children were multivitamins (15.6%), vitamin D (15.6%), fish oil (13.3%), omega-3 (11.1%), and probiotics (6.1%). As a result of multivariate logistic regression analysis, gender, number of siblings, age of the child, mother and father, education level of the mother and father, family type, and family income were not found to have a significant effect on the use of dietary supplements (p>0.050). Among the parents whose children use dietary supplements, 85.9% stated that they use them to make the child-resistant to diseases, 31.3% to make the child well-being, 26.6% to improve mental performance, and 10.9% to address a health problem. Conclusion: Approximately one-third of parents use dietary supplements to support their children’s immunity or improve their health. It should be remembered that there is very little data on the health benefits of dietary supplements in children with adequate and balanced nutrition and that unnecessary use may lead to negative consequences.